Establishment of a stable, effective and universal genetic transformation technique in the diverse species of Brassica oleracea - Xiaoguang Sheng; Huifang Yu; Jiansheng Wang; Yusen Shen; Honghui Gu (Frontiers in Plant Science, 2022)
Brassica oleracea is an economically important species, including seven cultivated variants. Agrobacterium-mediated transformation of B. oleracea crops, mainly via hypocotyl and cotyledon, has been achieved in the past. However, previously established transformation methods showed low efficiency, severe genotype limitation and a prolonged period for transformants acquisition, greatly restricting its application in functional genomic studies and crop improvement. In this study, we have compared the shoot regeneration and genetic transformation efficiency of hypocotyl, cotyledon petiole and curd peduncle explants from twelve genotypes of cauliflower and broccoli. Finally, an Agrobacterium-mediated transformation method using curd peduncle as explant was established, which is rapid, efficient, and amenable to high-throughput transformation and genome editing. The average genetic transformation efficiency of this method is stable up to 11.87% and was successfully implemented in twelve different genotypes of cauliflower and broccoli and other B. oleracea crops with low genotype dependence. Peduncle explants were found to contain abundant cambial cells with a strong cell division and shoot regeneration ability, which might be why this method achieved stable and high genetic transformation efficiency with almost no genotype dependence.